2023
DOI: 10.1002/lio2.1073
|View full text |Cite
|
Sign up to set email alerts
|

The effect of self‐management vestibular rehabilitation on persistent postural‐perceptual dizziness

Abstract: ObjectiveTo investigate the effects of self‐management vestibular rehabilitation (VR) on the subjective symptoms of dizziness and postural stability in persistent postural‐perceptual dizziness (PPPD).Study designRetrospective case review.MethodsThe medical records of 30 patients newly diagnosed with PPPD based on the Bárány Society's diagnostic criteria were reviewed. Nineteen patients (4 males and 15 females; age range 27–84 years, mean age ± standard deviation 57.4 ± 14.2 years) who was newly instructed to s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 20 publications
1
5
0
Order By: Relevance
“…Self‐management interventions were also described as an important therapeutic component. Our findings align with previous studies showing coping strategies can help patients to manage their lifestyle and gain a sense of control over their symptoms (e.g., identifying triggers, having a backup plan for unpredictable attacks) 27,70,71 . Our findings also brought another dimension to this discourse by highlighting barriers to self‐management implementation.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…Self‐management interventions were also described as an important therapeutic component. Our findings align with previous studies showing coping strategies can help patients to manage their lifestyle and gain a sense of control over their symptoms (e.g., identifying triggers, having a backup plan for unpredictable attacks) 27,70,71 . Our findings also brought another dimension to this discourse by highlighting barriers to self‐management implementation.…”
Section: Discussionsupporting
confidence: 89%
“…Our findings align with previous studies showing coping strategies can help patients to manage their lifestyle and gain a sense of control over their symptoms (e.g., identifying triggers, having a backup plan for unpredictable attacks). 27,70,71 Our findings also brought another dimension to this discourse by highlighting barriers to self-management implementation. Family members in our study thought that patients could have difficulties implementing strategies when their symptoms are severe.…”
Section: Loss Of Selfmentioning
confidence: 66%
“…Other experiences with self-care management over a period of 2 months have been documented in a retrospective case review [14]. In this study, 67% of patients diagnosed with PPPD, who were instructed to engage in a 2-month selfmanagement vestibular rehabilitation program, successfully completed the program, while 22% chose to discontinue the vestibular rehabilitation program at their own discretion [14].…”
Section: Upcoming Challengesmentioning
confidence: 74%
“…In this study, 67% of patients diagnosed with PPPD, who were instructed to engage in a 2-month selfmanagement vestibular rehabilitation program, successfully completed the program, while 22% chose to discontinue the vestibular rehabilitation program at their own discretion [14]. The authors reported that self-management vestibular rehabilitation led to a reduction in Dizziness Handicap Inventory scores and improvements in the Niigata PPPD questionnaire, which assesses subjective symptoms of dizziness [14]. However, this retrospective study indicated that patients who completed the self-care management program showed subjective improvements in dizziness symptoms but did not exhibit enhanced postural stability when objectively measured through posturography [14].…”
Section: Upcoming Challengesmentioning
confidence: 95%
See 1 more Smart Citation